ANALISIS PERAN STAKEHOLDER DALAM PENGEMBANGAN DESA WISATA “EKOWISATA TAMBAKSARI” KECAMATAN WANAREJA KABUPATEN CILACAP - Maya Wijayanti, Dwi; Djumiarti, Titik; Hayu Dwimawanti, Ida (Journal of Public Policy and Management Review, 2024)
The tourism sector has the potential to improve the quality of life for communities through increased tourism activities in Indonesia, both nationally and globally. Based on Provincial Regulation No. 2 of 2019 for Central Java, this regulation governs the development of tourist villages; however, in its implementation, several issues have been found indicating the suboptimal role of stakeholders in the "Tambaksari Ecotourism" Village in Wanareja District, Cilacap Regency. This study aims to identify and analyze the roles of stakeholders, as well as to identify obstacles to their roles. The research utilized a qualitative descriptive research method by collecting data through interviews and documentation. The results indicate that the stakeholder roles are less effective, with the identification of stakeholders consisting of Pokdarwis and Tambaksari Village as key players; DISPORAPAR as supporting stakeholders (contest setters); the Village Tourism Communication Forum as other followers (crowd); and PKK ANNUR TEFA as subject stakeholders. Stakeholder role identification shows that Pokdarwis is the implementor stakeholder; DISPORAPAR, Tambaksari Village, the Communication Forum, and PKK ANNUR TEFA are facilitator stakeholders; Tambaksari Village and the Village Tourism Communication Forum are coordinating stakeholders; and Tambaksari Village and the Village Tourism Communication Forum are accelerating stakeholders. Obstacles to stakeholder roles include technology use, stakeholder human resource competition, regulations, and stakeholder competency. Recommendations include providing training to stakeholder human resources and advocating for regulations in the development of tourist villages.